Biological Aspects of Goatfish (Upeneus spp) on Demak Waters - Suradi Wijaya Saputra; Prijadi Soedarsono; Gabriela Ari Sulistyawati (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2009)
Goatfish is one of the fishery resources which become a target species on demersal capturing activity with cantrang (Danish seine). The objectives of this research were to know biological aspect, i.e. sex ratio, growth, fecundity, average of length capture, and length of first maturity (Lm). The method used in this reseach was description survey. While collecting sample method by using a systematic random sampling method. Samples were held in TPI Morodemak, on Maret to April 2006. The result shaw that sex ratio was 1:1, and growth was negative allometric. Gonad maturities were dominated on level I. Total of fecundity range from 44.320 to 2.455.286 eggs. Avarage of length capture of male was 157 mm, and Lc and female was 164 mm. Length of first maturity of male was 216,44 mm, and female was 219,71 mm.  Key words : Goatfish, biological aspects, Demak waters